Centro de Capacitación y Entrenamiento Bomberil Caldas - Antioquia - Gutiérrez Figueroa, Stefanny (Arquitectura, Arte y Diseño, 2019)
This research is based on the expressed need by the voluntary fire service of the metropolitan area of Valle de Aburrá, to show new and better conditions for its volunteers and external services such as hiring and companies agreements. The objective is offer an excellent training and advice about the internal security. The fire brigades obtain resources from the contracts to sustain their centers. In order to respond this need was made a documentary and project field research. As a result was established the requirements that a fire training center should have for the proper development of body activities like how it works and what are the characteristics of the enviroment